1994
DOI: 10.1001/archinte.154.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Advance directives. Stability of patients' treatment choices

Abstract: Our findings generally support the use of advance directives. Most people made moderately stable decisions when using scenario- and treatment-specific directives, and stability improved after they reviewed the decisions, especially among those who had discussions with their physicians. Recent hospitalization did not decrease stability, although it appeared to reduce the improvement that others achieved with repeat interview. These findings suggest that advance directives can be relied on 1 to 2 years after com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
4

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 32 publications
4
77
0
4
Order By: Relevance
“…However, a follow-up study of the same cohort of outpatients demonstrated reasonable stability. 29 Another possibility is that family members or the physician may have been unaware of, or overrode the patient's preferences. 7,14,15 Some patients may wish to allow their physicians latitude when acting on their preferences, as other commentators have suggested.…”
Section: Discussionmentioning
confidence: 99%
“…However, a follow-up study of the same cohort of outpatients demonstrated reasonable stability. 29 Another possibility is that family members or the physician may have been unaware of, or overrode the patient's preferences. 7,14,15 Some patients may wish to allow their physicians latitude when acting on their preferences, as other commentators have suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The first is a series of studies that show how individuals' own preferences regarding lifesustaining treatment change over time. [10][11][12][13] In such studies, people are given health scenarios and asked whether they would want certain medical interventions. They are then resurveyed at later times.…”
Section: The Evidence Against Substituted Judgmentmentioning
confidence: 99%
“…These studies show that many individuals change their own wishes with regard to lifesustaining treatment over time. [10][11][12] In one study over half of patients who initially said yes to a series of medical procedures changed their minds over two years. 13 Furthermore, mindchanging is not random.…”
Section: The Evidence Against Substituted Judgmentmentioning
confidence: 99%
“…These values include preferences for autonomous versus shared decision making (Blackhall et al, 1995), concern for individual versus family or community interests (Klessig, 1992), beliefs in sanctity of life or possibility of miracles (Klessig, 1992), and personal ideas about what makes life worth living versus intolerable (Ditto, Druley, Moore, Danks, & Smucker, 1996). Although there is evidence that values-related variables do correspond to decision outcomes (Fischer, Alpert, Stoeckle, & Emanuel, 1997;Schonwetter, Walker, Solomon, Indurkhya, & Robinson, 1996), there is mixed evidence regarding the stability of and relationship between values and treatment preferences through time (Ditto et al, 2003;Emanuel, Emanuel, Stoeckle, Hummel, & Barry, 1994;Lockhart, Ditto, Danks, Coppola, & Smucker, 2001). …”
Section: Va Author Manuscriptmentioning
confidence: 99%